Another Look at the Glass and Smith Study on Class Size - James L. Phelps (Educational Considerations, 2011)
One of the most influential studies affecting educational policy is Glass and Smith’s 1978 study, Meta-Analysis of Research on the Relationship of Class Size and Achievement. Since its publication, educational policymakers have referenced it frequently as the justification for reducing class size.
Keywords: achievement; Glass and Smith Study; class size; research; measure; regression; equations